Incompatible ABO blood group renal transplant. Unprecedented collaborative experience between Spain and Peru - Méndez Chacón, Pedro (2017)
ABO blood group incompatibility and HLA sensitization are major barriers that need to be overcome in order to make optimum use of kidneys from living donors possible. We report the first successful ABOincompatible kidney transplant in a 24-year old, highly sensitized (panel reactive antibodies (PRA) 89% kidney retransplantation patient, who lacked any option to get a cadaveric or family donor. However, the patient’s sole HLA-compatible living donor had group A blood incompatible with the recipient’s O blood group. The patient required a pre-conditioning regime that consisted of plasma exchange, rituximab, immunoglobulin, and quadruple immunosuppressive therapy in order to reduce high titers of anti-A isoagglutinins from 1:128 to a safe level of 1:8, for successful transplant. This was performed in coordination with the Renal Transplant Unit of Hospital Clinic de Barcelona (HCB), Spain. Absence of rejection mediated by isoagglutinins shows the potential benefit of a protocol consisting in removing antibodies from the anti-blood group. Two years after transplantation, the kidney function remains stable, with creatinine levels of 1.5 mg%. We conclude that an ABO-incompatible kidney transplant is a viable option for patients whose only donor has blood of an incompatible blood group and for us this represents a hope-inspiring source of organs.